2022
DOI: 10.1098/rspb.2022.1819
|View full text |Cite
|
Sign up to set email alerts
|

Gene transferability and sociality do not correlate with gene connectivity

Abstract: The connectivity of a gene, defined as the number of interactions a gene's product has with other genes' products, is a key characteristic of a gene. In prokaryotes, the complexity hypothesis predicts that genes which undergo more frequent horizontal transfer will be less connected than genes which are only very rarely transferred. We tested the role of horizontal gene transfer, and other potentially important factors, by examining the connectivity of chromosomal and plasmid genes, across 134 diverse prokaryot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…For instance, we can use simple BLAST searches to identify extracellular proteins based on similarity to proteins known from lab assays to be secreted, or more sophisticated tools like PSORTb, which also looks at the presence of known sequence motifs (28). This method is the most established for finding cooperative genes, having been used in a number of studies (20)(21)(22)(23)(24)(25)49). One recent study of 51 diverse bacterial species found that on average ~2% of genes code for extracellular proteins (25).…”
Section: Extracellular Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, we can use simple BLAST searches to identify extracellular proteins based on similarity to proteins known from lab assays to be secreted, or more sophisticated tools like PSORTb, which also looks at the presence of known sequence motifs (28). This method is the most established for finding cooperative genes, having been used in a number of studies (20)(21)(22)(23)(24)(25)49). One recent study of 51 diverse bacterial species found that on average ~2% of genes code for extracellular proteins (25).…”
Section: Extracellular Proteinsmentioning
confidence: 99%
“…An alternative approach is to use bioinformatic tools to identify genes for cooperative behaviours (28)(29)(30)(31)(32)(33). Comparisons can then be made across species in order to examine how the number or proportion of cooperative genes varies, and if this can be explained by evolutionary theory (20)(21)(22)(23)(24)(25). For example, do species where interacting individuals are more likely to be clonally related have more cooperative genes (20)?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative approach is to use bioinformatic tools to identify genes for cooperative behaviours [20][21][22][23][24][25]. Comparisons can then be made across species in order to examine how the number or proportion of cooperative genes varies, and if this can be explained by evolutionary theory [26][27][28][29][30][31]. For example, do species where interacting individuals are more likely to be clonally related have more cooperative genes [26]?…”
Section: Introductionmentioning
confidence: 99%
“…These genes are likely to be for cooperative traits because the proteins can diffuse away from the cell. Any effect of the protein, such as breaking down food or neutralising antibiotics, can therefore provide benefits to the whole group of cells [27][28][29][30][31]. Another tool is PANNZER, which predicts the function of any gene based on sequence similarity to known proteins (a process known as 'functional annotation') [21].…”
Section: Introductionmentioning
confidence: 99%